Analysis of the Effect of Inflation and Per Capita Income on Household Consumption Expenditure in South Sulawesi Province - Lestari, Dini Indah; Basri Bado; Sri Astuty; Irwandi; Shadry Andriani (International Journal of Economics (IJEC), 2026)
This study aims to analyze the effect of inflation and per capita income on household consumption expenditure in South Sulawesi Province for the period 2015–2024. The research method used is a quantitative approach with a panel data regression model, using secondary data from the Central Statistics Agency (BPS) covering 12 districts/cities. The results of the Chow and Hausman test indicate that the most appropriate model to use is the Fixed Effect Model (FEM). The results of the regression analysis show that inflation has no significant effect on household consumption expenditure, while per capita income has a significant effect on household consumption expenditure. Simultaneously, both variables have a significant effect on household consumption with an Adjusted R² value of 50.72%, meaning that variations in consumption expenditure can be explained by inflation and per capita income. These findings indicate that increasing community income is the main factor driving consumption, while stable inflation helps maintain purchasing power and household economic balance in South Sulawesi